Impact of halal destination image, value, experience, contact on revisit intentions of Haul Sekumpul attendees - Dairobi, Muhammad; Anisah, Hastin Umi (Manajemen dan Bisnis, 2025)
This empirical study explores the factors influencing Muslim travelers’ satisfaction and their intentions to revisit in the context of halal tourism, focusing on the Haul Sekumpul event. Using Purposive Sampling, 313 participants aged 17 and above from various cities and educational backgrounds across Indonesia were engaged, providing a comprehensive perspective. The findings highlight that Tourism Experience and Perceived Value significantly impact both Satisfaction and Revisit Intentions, making them primary drivers for tourists' decisions to return. Conversely, Satisfaction, while crucial for immediate experience, did not determine Revisit Intentions, suggesting that contentment with the event does not ensure reattendance. Additionally, Halal Destination Image and Cultural Contact enhance Satisfaction but do not influence Revisit Intentions, indicating these elements alone are insufficient to compel repeat visits. Indirect effects of Halal Destination Image, Cultural Contact, Perceived Value, and Tourism Experience on revisit intentions, mediated by Satisfaction, showed no substantial predictive power. The study recommends that destination managers and marketers focus on enhancing perceived value and the richness of the tourism experience to drive repeat visitations, ensuring sustained engagement and loyalty within the halal tourism sector.